Discrimination and equality: Equal marriage in Advisory Opinion OC-24/17 of the Inter-American Court in Ecuador - Páez Bimos, Pedro (2019)
Advisory Opinion OC-24/17 of the Inter-American Court of Human Rights is of great importance to the region on paradigmatic issues such as gender identity, equality and non-discrimination for same-sex couples. This is the central point of reflection in the present essay, in which the principle of equality and non-discrimination to diverse sex-generic persons and the framework of equal marriage as a human right will be studied. Taking account, the discrimination of recent history that has been given to a minority little or nothing protected by the State.